Zambias HIV Response : Prioritised and Strategic Allocation of HIV Resources for Impact and Sustainability - World Bank (Washington, DC, 2015)
This report summarizes findings from an allocative efficiency and financial commitment analysis conducted for the Government of Zambia by the World Bank and the University of New South Wales. It uses Optima, a mathematical model of HIV transmission and disease progression. Optima is a population-based and flexible model, which provides a formal method of optimization and determines optimal allocations of HIV resources across numerous HIV programs, target populations, and funding levels. It also provides epidemic, investment scenario and financial commitment analysis.